Acute physical activity and cognitive performance: A focus on mediators and moderators - Valentin Benzing (Bern Open Publishing, 2023)
A growing body of research shows beneficial after effects of acute (i.e., single bouts of) physical activity on cognitive performance across different populations. Meta-analytic reviews typically find small effect sizes, however, the research in this area varies significantly regarding physical activity characteristics, measures of cognitive performance, investigated populations, and methodological strength of the work. Therefore, this symposium aims to look at potential mediators (e.g., physical activity characteristics, measures of cognitive performance, positive affect) and moderators (e.g., different populations) that might influence acute effects of physical activity on cognitive performance.